Building Services Audit & Inspection for Beginners - ABDUL RAHMAN , MOHAMMAD ASHRAF; MUSTAFA, MOHD SYAFIQ SYAZWAN (2024)
Building services such as heating, ventilation, air conditioning, lighting, plumbing and electrical systems are vital for a building’s functionality, safety and efficiency. However, they require regular monitoring and maintenance to meet evolving standards. Auditing and inspecting building services is an opportunity to create positive change. By uncovering inefficiencies and enhancing occupant comfort, you contribute to sustainable, resilient and healthy built environments. Approach each chapter with curiosity and embrace the principles outlined in this book. Building services audit and inspection is a dynamic field, and this resource serves as a foundation for ongoing growth and profesional development.